Exploring oxidative modifications of tyrosine: An update on mechanisms of formation, advances in analysis and biological consequences - YILMAZ, BETÜL (TAYLOR & FRANCIS LTD, 2015)
Protein oxidation is increasingly recognised as an important modulator of biochemical pathways controlling both physiological and pathological processes. While much attention has focused on cysteine modifications in reversible redox signalling, there is increasing evidence that other protein residues are oxidised in vivo with impact on cellular homeostasis and redox signalling pathways. A notable example is tyrosine, which can undergo a number of oxidative post-translational modifications to form 3-hydroxy-tyrosine, tyrosine crosslinks, 3-nitrotyrosine and halogenated tyrosine, with different effects on cellular functions. Tyrosine oxidation has been studied extensively in vitro, and this has generated detailed information about the molecular mechanisms that may occur in vivo. An important aspect of studying tyrosine oxidation both in vitro and in biological systems is the ability to monitor the formation of oxidised derivatives, which depends on a variety of analytical techniques. While antibody-dependent techniques such as ELISAs are commonly used, these have limitations, and more specific assays based on spectroscopic or spectrometric techniques are required to provide information on the exact residues modified and the nature of the modification. These approaches have helped understanding of the consequences of tyrosine oxidation in biological systems, especially its effects on cell signalling and cell dysfunction, linking to roles in disease. There is mounting evidence that tyrosine oxidation processes are important in vivo and can contribute to cellular pathology.
Keywords: tyrosine oxidation; tyrosine nitration; oxidising free radicals; redox balance; time resolved techniques; mass spectrometry; antibody-dependent techniques; INTRAMOLECULAR ELECTRON-TRANSFER; TANDEM MASS-SPECTROMETRY; REDOX-ACTIVE TYROSINES; PROTEIN-BOUND 3,4-DIHYDROXYPHENYLALANINE; SARCOPLASMIC-RETICULUM CA2+-ATPASE; PEROXYNITRITE-MEDIATED NITRATION; MANGANESE SUPEROXIDE-DISMUTASE; PROSTAGLANDIN-H SYNTHASE; DITYROSINE CROSS-LINKING; CYTOCHROME-C-OXIDASE